Towards a sustainable future: The interplay of trade globalization and regulatory quality on environmental outcomes in India - Nupur Soti; Ashish Kumar; Sanjeev Gupta; Suman Ahuja; Deepa (Sustainable Futures)
Over the past three decades, India's transformative journey through globalization has boosted trade and technological advancements but has also raised concerns about balancing development with environmental sustainability, emphasizing the urgent need for stringent environmental regulations. In this context, this study investigates the impact of trade globalization (TG) and regulatory quality (RQ) on ecological footprints (EF) in India from 1990 to 2022. Additionally, economic growth (EG), urbanization (UB), and biocapacity (BC) are included as control variables to eliminate the possibility of omitted variable bias. The Autoregressive distributive lag (ARDL) and Quantile autoregressive distributed lag (QARDL) methodologies are employed to unravel this nexus. The study utilizes three different models for robust explorations of the impact of TG and RQ on EF. The findings are consistent across both the techniques for all these models, underscoring the validity of our results. Specifically, our findings reveal a significant inverse relationship between TG and EF (in the short-run) and between RQ and EF (in the short-run and long-run). This validates the pollution halo effect hypothesis (PHEH) in India in the short-run, suggesting that stringent regulations can promote ‘clean’ trade in the host nation. Additionally, the interaction effect of TG and UB on EF is statistically significant, highlighting the importance of integrating trade and environmental policies to foster green growth. Based on the findings, the study offers important policy implications.